2003
DOI: 10.1590/s0102-76382003000200007
|View full text |Cite
|
Sign up to set email alerts
|

Molecular evaluation of the great vessels of patients with bicuspid aortic valve disease

Abstract: Abstract:Purpose: Bicuspid aortic valve (BAV) is associated with increased prevalence of annulo-aortic ectasia, dissection and ascending aortic aneurysm. This study was undertaken to compare the amount of fibrillin-1 and elastin in the media of great vessels of patients with bicuspid and tricuspid aortic valve disease. Method: Tissue samples of ascending aorta and pulmonary artery were obtained from 22 patients with bicuspid aortic valve disease (BAV) and 17 patients with tricuspid aortic valve disease (TAV), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…A deficiency of fibrillin has been associated with BAV disease [ 53 ]. Studies comparing BAV and TAV AAo specimens identified a decrease in fibrillin-1 in BAV patients, which may contribute to explaining aortic root dilation and AAo dissection in these patients [ 54 , 55 ]. In two studies of BAV, TAV, and Marfan patients, both Marfan and BAV showed a differential distribution and decreased fibrillin-1 expression in the aorta, as well as significant decrease in differentiated SMC markers, suggesting a maturation defect of the aortic wall [ 38 , 39 , 56 ].…”
Section: Tissue Biologymentioning
confidence: 99%
“…A deficiency of fibrillin has been associated with BAV disease [ 53 ]. Studies comparing BAV and TAV AAo specimens identified a decrease in fibrillin-1 in BAV patients, which may contribute to explaining aortic root dilation and AAo dissection in these patients [ 54 , 55 ]. In two studies of BAV, TAV, and Marfan patients, both Marfan and BAV showed a differential distribution and decreased fibrillin-1 expression in the aorta, as well as significant decrease in differentiated SMC markers, suggesting a maturation defect of the aortic wall [ 38 , 39 , 56 ].…”
Section: Tissue Biologymentioning
confidence: 99%
“…It has been noted that the fibrillin-1 content was remarkably reduced in the aorta of BAV patients, compared with that of patients with a tricuspid aortic valve. Aortic elasticity measurements of BAV patients suggest that diminished aortic elasticity is at least part of its causation [23][24][25].…”
Section: Embryology and Pathogenesismentioning
confidence: 99%